Moiré superlattice engineering of two-dimensional materials for electrocatalytic hydrogen evolution reaction - Li, Yang; Hua, Yuqi; Sun, Ning; Liu, Shijie; Li, Hengxu; Wang, Cheng; Yang, Xinyu; Zhuang, Zechao; Wang, Longlu (Nano Research, 2023)
Vertically stacking two-dimensional (2D) materials with small azimuthal deviation or lattice mismatch generate distinctive global structural periodicity and symmetry, revealed as the moiré superlattices (MSLs). Manipulating the interlayer twist angle enables the modification of the electronic structure of 2D materials to explore the advanced applications. Although extraordinary progress has been achieved in the unique structure and emergent properties of MSLs, the investigation of the catalytic applications of MSLs materials is still in its infancy. It is therefore very urgent to summarize the advanced development of MSLs in the field of catalysis. In this review, we firstly summarize the advanced fabrication and high-resolution characterization techniques of the MSLs materials, as well as their novel properties related to catalysis represented by electrocatalytic hydrogen evolution reaction (HER). Then, all the MSLs materials such as MoS 2 , WS 2 , and Ru serving as electrocatalysts for HER are further reviewed in detail. Finally, we outline the current challenges as well as the experimental and theoretical strategies to advance the development of function-oriented MSLs materials for catalysis. This review aims to provide profound insight into the wide applications of this novel material platform in catalytic field.